Biopolymeric-based emulsions and their effects during processing, digestibility and bioaccessibility of bioactive compounds in food systems. (February 2019) - Anal, Anil Kumar; Shrestha, Smriti; Sadiq, Muhammad Bilal
Abstract: This article reviews the major type of interactions between proteins and polysaccharides which occur either by covalent bonding or non-covalent interactions. Covalent interactions are specific and occur due to glycosylation of amino group of proteins and carboxylic group of polysaccharides, while non-covalent interactions are non-specific and generally occur via electrostatic interaction, hydrogen bonding, hydrophobic and van der Waals interactions. Furthermore, this review presents the recent research conducted on the development of various proteins (animal, milk, egg, and plant based proteins)-polysaccharide conjugates, their functional properties as emulsifiers and industrial applications. Recent applications of the protein-polysaccharide conjugates to encapsulate, protect, improve bioavailability and control delivery of bioactive components are also discussed. Graphical abstract: Image Highlights: Covalent and non-covalent interaction mechanisms between proteins and polysaccharides. Recent progress in interactions between animal proteins and plant-based proteins with polysaccharides. Protein-polysaccharide conjugate applications in emulsion stabilization, controlled and targeted delivery.